Sesame Nutrient Diagnosis and Balance Using Diagnosis and Recommendation Integrated System in Response to Co-Applied Fertilizers - Mahmood, Muslim Sleman; Rasheed Dizayee, Alwand Tahir (Kurdistan Journal of Applied Research, 2026)
Diagnosis and Recommendation Integrated System (DRIS) is a practical and repeatable complimentary method for nutritional diagnosis in various crops. The current study was conducted during the spring growing season of 2024 at the Halabja Agriculture Research Centre, located in the northwest of Halabja city (latitude: 38° 58.95΄ N, longitude: 45°69.56΄ E) at an altitude of 595 m. The experimental field was a vertisol with a clay texture. The study was based on three independent variables: four levels of biofertilizer application, including (control, individual inoculation of Azospirillum + Azotobacter, phosphate solubilizing bacteria, and combined bacterial treatment), three rates of nitrogen (N)-phosphorus (P)-potassium (K) fertilizer (0, 100, and 140 kg ha⁻¹), and three doses of olive mill pomace (0, 15 and 30 megagram (Mg) ha⁻¹) as organic amendment. A split-split plot design was used with 36 treatment combinations arranged in three replications. Yield component and plant nutrient balance data were processed using the DRIS. The results identified the combination of nitroxin, NPK at 100 kg ha-1, and olive mill pomace at 30 Mg ha-1 (BNCH1OR2) as the most nutritionally balanced treatment (Nutrient Balance Index = 5.16), which concurrently produced the highest grain yield (0.96 Mg ha-1, 100% relative yield). In contrast, the most unbalanced treatment was the control condition (without biofertilizer, chemical fertilizer, and olive mill pomace), with a nutrient balance index of 82.32, yielded the lowest output (0.41 Mg ha-1, 43% relative yield). For N, P, and K, the critical points were determined as 2.15, 0.23, and 1.68, respectively. Nutritional balance indices and sesame yield as altered by biofertilizer, NPK, and organic fertilization, indicate that the BNCH1OR2 treatment was particularly effective for enhancement of nutrient balance and grain yield.